Potensi Retribusi Parkir Di Kabupaten Sumba Timur - Umbu Ho Ara; Erfan Kristio Koreh (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2014)
This paper aims to analyze the potential and constraints in the collection of parking retribution in East Sumba. The data used are primary data and secondary data. The findings of this study: (1) Potential parking retribution in East Sumba in 2014 amounted to Rp. 733.864 million. While the average realized revenue per year, in previous years amounting to Rp 6.7785 million, or only 0.92 percent of the total potential parking retribution. These conditions indicate the realization of income is very small when compared to the available potential, (2) Realization of the small reception, due to some constraints as follows: a) The absence of regulations governing the implementation of the levy charged for parking. for example, unclear deductions from wages for officers collected parking fees collector. b) The lack of socialization about parking regulations in East Sumba. This can be seen from the lack of public understanding of regulations, systems and procedures that parking fees adversely affects the attitude of the orderly administration of the parking service. c) The low quality of security and inadequate facilities. This is evidenced by the availability of parking space is inadequate, the lack of security vehicles at the parking lot. d) the lack of resources or the capabilities of retribution parking attendant collector.Keywords: own source revenue, parking retribution.